Incidence and patterns of late recurrences in colon cancer patients. Issue 9 (6th May 2015) - Bouvier, Anne‐Marie; Launoy, Guy; Bouvier, Véronique; Rollot, Fabien; Manfredi, Sylvain; Faivre, Jean; Cottet, Vanessa; Jooste, Valérie
<x xml:space="preserve">Abstract</x> Long‐term recurrences of colon cancer raised questions about the possible benefit of prolonging the recommended active 5‐year surveillance. The aim of this study was to determine, for the first time, the incidence and patterns of late 10‐year recurrence following curative resection of colon cancer. Data were obtained from two French digestive cancer registries. A total of 3, 622 patients under 85 years resected for cure for colon cancer diagnosed between 1985 and 2000 were included. Information regarding recurrences was actively collected. Cumulative failure rates at 10 years were estimated using Kaplan–Meier estimates corrected by cause‐specific hazards, and multivariable analysis was performed using a model for the subdistribution of a competing risk proposed by Fine and Gray. The overall cumulative recurrence rate between 5 and 10 years after initial surgery was 2.9% for local recurrence and 4.3% for distant metastasis. Among men with no recurrence 5 years after diagnosis of colon cancer, 1 in 12 developed a recurrence between 5 and 10 years, and the corresponding cumulative rate was 7.8%. The frequency was 1 in 19 for women, corresponding to a cumulative rate of 5.2%. In the multivariate analysis, non‐emergency diagnostic feature, female sex and age under 75 were associated with a lower risk of recurrence. Stage at diagnosis was not a predictor of late recurrence. Late recurrence after colon cancer resection with curative intent can occur. A regular clinical follow‐up is necessary to detect early signs of possible recurrence.